Single-Cell Analysis of Human Ovarian Cortex Identifies Distinct Cell Populations But No Oogonial Stem Cells. Issue 6 (June 2020) - Wagner, Magdalena; Yoshihara, Masahito; Douagi, Iyadh; Damdimopoulos, Anastasios; Panula, Sarita; Petropoulos, Sophie; Lu, Haojiang; Pettersson, Karin; Palm, Kerstin; Katayama, Shintaro; Hovatta, Outi; Kere, Juha; et al.
Abstract : (Abstracted from Nat Commun 2020;11:1147) In the female fetus, oogonia derived from fetal germ cells (FGCs) form primordial follicles that remain dormant until reactivation in the postnatal ovary. The reserve of primordial follicles in the ovarian cortex determines the fertile lifespan, and its depletion marks the beginning of menopause.